Entre demagogismo e soberania popular : o voto do analfabeto nos jornais Folha de S. Paulo e Estado de S. Paulo (1981-1985) - Zajaczkowski, Jéssica Schaefer (2021)
Approved Constitutional Amendment No. 25 in 1985, the illiterate vote becomes part of the country's electorate. Since 1824, different norms have come to focus on the Brazilian electoral system, establishing qualifying criteria for the exercise of the vote. In 1881, after the “Saraiva Law”, the illiterate person was excluded from the electorate as a result of the requirement of a literate vote, leaving the country with one of the smallest electorates compared to its population, between 1.5%. In 1945, this percentage had surpassed 15%, reaching 33% in the 1970s. The 50% mark was only surpassed from the 1980s onwards with the country's redemocratization in parallel with the consolidation of the illiterate vote, 104 years after your exclusion. From this problematic exposed, this research arises, concerned with understanding this late relationship, aiming to analyze the discourses produced in the Brazilian press of that period, specifically in the newspapers Folha de S. Paulo and O Estado de S. Paulo on the vote of illiterate people in redemocratization of the country. These speeches explained different elaborations about the agenda, showing conflicts and tensions around its consolidation, deeply associated with the different transformations that were at stake in the transition from the military to the democratic regime, in the construction of the Democratic State of Law that established a new Constitution Federal for the country, in 1988. In the constitutional text and in the discourses explored, there is no hegemonic construction around the subject, on the contrary, there is strong tension, resulting in the guarantee of the illiterate vote and, at the same time, establishing it on an optional basis, without the right to enlistment and eligibility.